Political representation and empowerment of Roma in Slovenia - Zevnik, Andreja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
Some democratic societies use reserved representation mechanisms to address the underrepresentation of marginalised minority groups. We analyse the case of Slovenian Roma - a marginalised minority group afforded limited representational rights by the state. Drawing on the theoretical framework of reserved representation and minority rights, we argue that extending reserved representational rights for Roma to the national level would correct a fundamental institutional design oversight. It would constitute a significant step towards recognising Roma as a minority and an equal political actor in Slovenia and create an opportunity for political empowerment of the community and allow Roma to begin to address their socio-economic marginalisation.
Keywords: manjšina; marginalizacija; rezervirano politično predstavništvo; Romi; Slovenija; slovenski parlament